De las costumbres y conversión de los indios del Perú memorial a Felipe II (1588) - Alvarez, Bartolomé. (Crónicas y memorias, 1998)
A memorial to King Philip II of Spain, written in 1587-1588, requesting that the Inquisition be brought to the indigenous peoples of the Andes. This critical edition includes essays about the author, the geography history and languages of the Pampas Aullagas region, and the text itself, with commentary.